Eleições municipais e profissionalização das campanhas eleitorais (São Paulo, 2016) - Alves, Mércia Kaline Freitas (Universidade Federal de São Carlos, 2020)
This thesis aims to discuss how the professionalization of election campaigns was incorporated and developed at the municipal level. The survey walked from the questions: Has the process of professionalization, described by international literature and in Brazil, reached the majority campaigns in the municipalities? If in positive case so, how and what are the characteristics of this process in local election campaigns? How is the physical structure of the parties and the number of people involved to carry out paid and voluntary activities during the election period expanded? Finally, how are the financial resources of the parties and coalitions allocated and distributed in campaign management? To answer these questions, 12 election campaigns were selected in six municipalities (2016), chosen according to size and access to HGPE. We examined the financial dynamics of each campaign, and conducted interviews with candidates, party coordinators and/or leaders. They are: Campinas, PT and PHS campaigns; Guarulhos, PSB and DEM; Santos, PCdoB and PSDB; Diadema, PT and PV; Jau, PSoL and REDE; and in Botucatu, PDT and PSDB campaigns. The data were analyzed in order to obtain the vision of the leaders about the organization of the campaigns, the selection of candidates to define the strategies.
Municipal elections and professionalization of electoral campaigns (São Paulo, 2016)
Keywords: Campanhas eleitorais; Partidos e eleições; Profissionalização das campanhas eleitorais; Eleições municipais; Electoral campaigns; Parties and elections; Professionalization of electoral campaigns; Municipal elections; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO